Perbedaan Gejala Konjungtivitis Pada Karyawan Terpapar Debu Batubara di Atas NAB dan Di bawah NAB di PT INDO ACIDATAMA tbk Kemiri, Kebakkramat, Karanganyar - Susanto, Erwan (2016)
The coal dust came from the process of destruction and separation of coal that causes health problems such as conjungtivitis. The sources of exposure to coal dust in PT. Indo Acidatama, Tbk came from the work process in unit crusher. The purpose of this study was to know the differences symptomps of conjungtivitis in employees exposed by coal dust above and below the thershold value in PT. Indo Acidatama Tbk. The method used observational research with cross sectional approach. Sample's Technique used sample total sampling method with 24 Respondences which were consisted 12 employees from crusher and 12 employees from mechanical workshop. The result of this study used the mann-whitney statistic test showed significant (p 0.000 <0.05), its means there was differences symptomps of conjungtivitis in employees exposed by coal dust above and below the thershold value in PT. Indo Acidatama Tbk. Based on the result, in crusher unit was found 50% employees exposed to moderate symptomps of cojungtivitis and 50% employees exposed to severe symptomps of conjungtivitis. While in mechanical workshop unit, 75% employees exposed to moderate symptomps of conjungtivitis and 25% employees exposed to severe symptomps of conjungtivitis. To reduce symptoms of conjungtivitis, workers should use personal protective equipment completely such as goggles that should provided by companies.